Shear properties of three‐dimensional woven composite reinforcements. Issue 2 (13th May 2015) - Sun, Fei; Zhang, Yifan; Chen, Li; Zhang, Meiling; Pan, Ning
Abstract : This paper presents a comprehensive experimental study and detailed mechanistic interpretations of the shear deformation of three‐dimensional (3D) reinforcements. Six types of 3D angle interlock glass fiber preforms (3DAP) were fabricated using a range of weave parameters including the fabric density, fabric layer, and yarn linear density. A modified picture frame was developed to ensure a pure shear load during the test. Through a series of comprehensive tests, our results demonstrated that the fabric density played a key role in the mechanical properties of 3DAP and that the reinforcements with low fabric density and yarn linear density were easy to shear. The shear deformation mechanism was analyzed based on the meso‐structure. It is expected that this research will provide preliminary work for building a theoretical model of 3D woven preform. POLYM. COMPOS., 38:244–251, 2017. © 2015 Society of Plastics Engineers